LC-MS/MS simulatneous determination of itopride hydrochloride and domperidone in human plasma - Bose, Anirbandeep; Bhaumik, Uttam; Ghosh, Animesh; Chatterjee, Bappaditya; Chakraborty, Uday Sankar; Sarkar, Amlan Kanti; Pal, Tapan Kumar (Vieweg Verlag, 2009)
A rapid, simple, sensitive and specific liquid chromatography–tandem mass spectrometry method was developed and validated for simultaneous quantification of itopride hydrochloride and domperidone in human plasma. Both drugs were extracted by liquid–liquid extraction with ethyl acetate and saturated borax solution. The chromatographic separation was performed on a reversed-phase C18 column with a mobile phase of water–methanol (2:98, v/v) containing 0.5% formic acid. The protonated analyte was quantitated in positive ionization by multiple reaction monitoring with a mass spectrometer. The assay exhibited linearity over the concentration range of 3.33–500 ng mL−1 for itopride hydrochloride and 3.33–100 ng mL−1 for domperidone in human plasma. The precursor to product ion transitions of m/z 359.1–72.3 and 426.0–147.2 were used to measure itopride hydrochloride and domperidone respectively. The method was found suitable for the analysis of plasma samples collected during phase 1 pharmacokinetics study of itopride HCl 50 mg and domperidone 20 mg in 12 healthy volunteers after single oral doses of the combination drug.